1995
DOI: 10.1007/bf01857658
|View full text |Cite
|
Sign up to set email alerts
|

Family history of hypertension and vasovagal symptoms during blood donation

Abstract: Vasovagal reactions during blood donation were assessed in 185 individuals with and 298 individuals without a parental history of hypertension. It was predicted that individuals at genetic risk for hypertension would be less likely to faint or suffer pronounced vasovagal reactions, presumably by virtue of altered baroreflex sensitivity. A relationship between a parental history of hypertension and vasovagal responses was observed, albeit modified by blood donation experience and sex. Nurses obtaining blood fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Two options are available to reduce the observational effect: (a) Reduce the number of donors fainting, and (b) reduce the visibility of donors fainting. Reducing the number of donors fainting could be achieved by either screening for risk factors (e.g., Ditto, Adler, France, & France, 1995; France, 1995; Labus, France, & Taylor, 2000; Trouern-Trend, Cable, Badon, Newman, & Popovsky, 1999) or using prophylactic interventions (e.g., Sauer & France, 1999). Simply rearranging the donor site using screens to partition areas should reduce visibility.…”
Section: Discussionmentioning
confidence: 99%
“…Two options are available to reduce the observational effect: (a) Reduce the number of donors fainting, and (b) reduce the visibility of donors fainting. Reducing the number of donors fainting could be achieved by either screening for risk factors (e.g., Ditto, Adler, France, & France, 1995; France, 1995; Labus, France, & Taylor, 2000; Trouern-Trend, Cable, Badon, Newman, & Popovsky, 1999) or using prophylactic interventions (e.g., Sauer & France, 1999). Simply rearranging the donor site using screens to partition areas should reduce visibility.…”
Section: Discussionmentioning
confidence: 99%
“…Donor inexperience may be one important factor that may contribute to vasovagal responses during blood donation. For example, it has been shown that nurses obtaining blood from inexperienced donors without a parental history of hypertension were significantly more likely to recline the subject's chair than those obtaining blood from inexperienced donors with a parental history of hypertension or experienced donors (Ditto, Adler, France, & France, 1995). Generally, less experienced blood donors reported more vasovagal symptoms than experienced donors, and this corresponds to higher rates of treatment by the nurses, more fainting, and fewer full units of blood obtained (Byrne & Ditto, 2005).…”
mentioning
confidence: 99%
“…En un estudio se informó la relación inversa entre la historia familiar de hipertensión y la respuesta vasovagal durante la donación (9).…”
Section: Resultsunclassified